The Beidou high precision geological disaster monitoring system based on RTK edge calculation and its application analysis - Zhen ZHU; Siyi JIANG; Xiaoming LIU; Zhiyu LI (Shuiwen dizhi gongcheng dizhi, 2021)
To provide service of all-weather, full automation and high precision deformation monitoring and to furthest reduce the effects of space environment factors on the high precision real-time positioning, on the digital CDRadio edge of RTK GNSS core analytic computing technology fusion algorithm is used, and “the Beidou high-precision geological disaster monitoring system with edge calculation based on broadcasting RTK”is developed, which is characterized by the independent intellectual property rights and structure open. The system can run stably for a long time, and can satisfy the functional requirements and non-functional requirements of all users. Taking the unstable slope of block 8 in the Gemstone Garden in Changzhou District of Wuzhou as an example, the monitoring results from May to November 2020 are analyzed. The monitoring data show that the whole slope body is in the stage of slow development, and the front edge of the slope top has a tendency of peristatically moving and sinking. The whole slope body tends to develop towards the southeast direction. Through the establishment of a good system information interaction platform, the statistical analysis information formed by the system is transmitted to users in a high speed and convenient way, which effectively improves the users' system management, decision-making and application ability. It can fully mine the data resources of the system, provide real-time forecasting services, effectively improve the accuracy and reliability of information collection, transmission, processing, analysis and forecast, comprehensively improve the ability of geological disaster monitoring, early warning and forecast management, and better provide scientific basis for the decision-making and command of management departments at all levels in emergency rescue and disaster relief.